Kualitas Layanan, Citra dan Pengaruhnya terhadap Loyalitas melalui Kepuasan Pelanggan (Studi Pada PT Bank Bni 46 Sentra Kredit Kecil Surabaya) - Saputra, Falla Ilhami (Jurnal Aplikasi Manajemen, 2013)
The purpose of this study was to determine whether the quality of services can significantly affect customer satisfaction, to determine whether the image and service quality can significantly affect customer satisfaction, to determine whether the image and customer satisfaction can significantly affect customer loyalty, to determine whether customer satisfaction can significantly affect customer loyalty, to determine whether citran and service quality can significantly affect customer loyalty mediated by customer satisfaction. The result showed that Image positive and significant impact on customer satisfaction with the value (B) of 0,560. Service Quality positive and not significant impact on loyalty with the value (B) of 0,107. Image negative and significant impact on loyalty with the value (B) of -0,306. Customer satisfaction positive an significant impact on loyalty with the valeu (B) of 0,857. The indirect significant of service quality on loyalty through customer satisfaction of 0,243 and Image on loyalty through customer satisfaction of 0,480.